Impact of Aortic Diameter Measurements at Three Anatomical Landmarks on Left Ventricular Output Calculation in Neonates. (23rd August 2021) - Ficial, Benjamim; Bonafiglia, Elena; Gangemi, Antonella; Clemente, Maria; Cappelleri, Alessia; Corsini, Iuri; Biban, Paolo
Abstract : Objectives: To assess reproducibility and accuracy of left ventricular output (LVO) quantifications in neonates, when left ventricular outflow tract diameter (LVOTD) was measured at the hinges of the aortic valve (AV), at the aortic sinus (AS), and at the sinotubular junction (STJ). Methods: This was an observational study. In the first cohort of very preterm neonates, we assessed intraobserver and interobserver repeatability of LVOTD measured at the AV, AS, and STJ and of the corresponding LVO. In the second cohort of older neonates, we compared paired LVO measurements by echo and magnetic resonance imaging (MRI). Results: In the first cohort of 48 neonates, mean (standard deviation) weight and age at scan were 1046 (302) g and 28.1 (2.7) weeks. Interobserver bias (95% limits of agreement [LOA]) for LVOTD at the AV, AS, and STJ was 0 (−0.3 to 0.3) mm, 0 (−0.7 to 0.7) mm, and 0 (−0.8 to 0.7) mm, respectively. Interobserver bias (95% LOA) for the corresponding LVO was −1.3 (−31 to 33) ml/kg/min, −0.5 (−88 to 87) ml/kg/min, and −7.2 (−83 to 69) ml/kg/min, respectively. In the second cohort of 10 neonates, median (range) weight and age at scan were 1942 (970–3640) g and 37.2 (31.7–39.8) weeks. LVO measured at the AV showed stronger agreement with MRI: bias (LOA) −10.6 (−74 to 52) ml/kg/min, compared to LVO measured at AS and STJ: 194 (−0.5 to 388) ml/kg/min and 43 (−72 to 159) ml/kg/min respectively. Conclusions: Reproducibility and accuracy of LVO quantification by echo were better when aortic diameter was measured at AV.